2015
DOI: 10.1038/cdd.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like protein p32 regulates ULK1 stability and autophagy

Abstract: Mitophagy mediates clearance of dysfunctional mitochondria, and represents one type of mitochondrial quality control, which is essential for optimal mitochondrial bioenergetics. p32, a chaperone-like protein, is crucial for maintaining mitochondrial membrane potential and oxidative phosphorylation. However, the relationship between p32 and mitochondrial homeostasis has not been addressed. Here, we identified p32 as a key regulator of ULK1 stability by forming complex with ULK1. p32 depletion potentiated K48-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Silencing p32 profoundly impairs starvation-induced autophagic flux and clearance of damaged mitochondria caused by a mitochondrial uncoupler. These findings support a cytoprotective role for p32 under starvation conditions by regulation of ULK1 stability, and reveal a crucial involvement of the p32-ULK1-autophagy axis in coordinating the stress response, cell survival and mitochondrial homeostasis (69). Mammalian RNase H1 is implicated in mitochondrial DNA replication and RNA processing and is required for embryonic development.…”
Section: An Important Question Is What Is the Primary Function Of P32supporting
confidence: 60%
“…Silencing p32 profoundly impairs starvation-induced autophagic flux and clearance of damaged mitochondria caused by a mitochondrial uncoupler. These findings support a cytoprotective role for p32 under starvation conditions by regulation of ULK1 stability, and reveal a crucial involvement of the p32-ULK1-autophagy axis in coordinating the stress response, cell survival and mitochondrial homeostasis (69). Mammalian RNase H1 is implicated in mitochondrial DNA replication and RNA processing and is required for embryonic development.…”
Section: An Important Question Is What Is the Primary Function Of P32supporting
confidence: 60%
“…The interaction of UL47 with p32 was confirmed in HSV-1-infected cells: p32 coprecipitated with MEF-tagged UL47 in lysates of cells infected with recombinant virus YK536 (MEF-UL47). p32 is a ubiquitous protein in most cell types and a multifunctional protein regulating various cellular functions, including apoptosis, RNA splicing, mitochondrial translation and metabolism, and autophagy (27,(59)(60)(61)(62). We also found that p32 accumulated at the nuclear rim in HSV-1-infected cells and that UL47 was required for the p32 accumulation.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, the chaperone protein p32 binds ULK1 and, acting by an unknown E3 ligase, inhibits Lys-48-linked ubiquitination while driving Lys-63-linked ubiquitination. This promotes ULK1 stability and is crucial in both starvation-induced autophagy and mitophagy ( 28 ), the selective removal of mitochondria. In another context, ubiquitination negatively regulates ULK1 signaling ( 29 31 ).…”
Section: Sensing the Signalmentioning
confidence: 99%